Preparation of Portland Cement with Gold Ore Tailings - Qiang Wang; Geng Yao; Xiangnan Zhu; Junxiang Wang; Peng Wu; Xianjun Lyu (Advances in Materials Science and Engineering)
The disposal of gold ore tailings (GTs) has been a very difficult problem for a long time. Thus, this study explored a new approach to the management of GTs by preparing Portland cement. Physical properties, reaction mechanisms, and hydration product types of cement prepared with GTs (C-GTs) and ordinary Portland cement (C-SS) were compared. X-ray diffraction (XRD), thermogravimetric (TG), and scanning electron microscope energy-dispersive spectroscopy (SEM-EDS) analysis techniques were used to study the mineralogical phases of the clinker and raw materials, hydration product types, and microtopography. The consistency, setting time, flexural strength and compressive strength values of the cement samples (C-GTs and C-SS), and burnability of the raw materials were also studied. The burnability analysis indicated that GTs provided a higher reactivity. The XRD results showed that the clinker phases of the C-GTs were C3S, C2S, C3A, and C4AF. The XRD, TG, and SEM-EDS results showed that the hydration products were flaky calcium hydroxide, rod-shaped ettringite, and granular C-S-H gels. Its compressive strength and flexural strength were, respectively, 30.4 MPa and 6.1 MPa at the curing age of 3 days and 59.1 MPa and 9.8 MPa at the curing age of 28 days, which were slightly higher than those of the C-SS. Furthermore, the results showed that the consistency, initial setting time, and final setting time for the two kinds of cement were similar, which further suggested that GTs could be used to prepare Portland cement.